Editorial - Abdelaal, Mostafa; Grilli, Matteo (Southern Journal for Contemporary History, 2023)
We are glad to announce a new associate editor that will join us starting with the current issue. His name is Mostafa Abdelaal, Assistant Professor (Lecturer) at the Department of History, Faculty of African Postgraduate Studies, Cairo University. Mostafa obtained his PhD from the Faculty of History at Cambridge University. He is currently working on turning his PhD dissertation into a book that investigates the roles of State, Resources and Modern Manufacturing in Zambia from 1924 to 1992. He recently published a book in Arabic titled Colonial Exploitation and Economics of Rubber in the Congo Free State, 1885-1908. Mostafa’s research interest is on the economic history of Africa, economic aspects of Afro-Arab history, and the questions of industrialisation and economic development.